The Role of External and Internal Factors in Determining the NAV Movement of Sharia Mutual Funds - Riska Adetya; Mutia Sumarni; Tajul ‘Ula; Rahmini Hadi; Mustaniroh (Mabsya: Jurnal Manajemen Bisnis Syariah, 2025)
This study investigates the factors influencing the performance of Islamic Balanced Mutual Funds in Indonesia, with a specific focus on fluctuations in Net Asset Value (NAV). The declining growth of these funds is hypothesized to be associated with a weakening macroeconomic environment. External variables considered in this study include inflation and the Bank Indonesia benchmark interest rate (BI Rate), while internal variables encompass trading volume and transaction timing. The objective is to examine the impact of both internal and external factors on the NAV performance of Islamic Balanced Mutual Funds. The sample consists of two actively managed Islamic mutual funds operating between 2016 and 2023. Panel regression analysis is employed to evaluate the relationships. The findings reveal that internal and external factors jointly influence NAV performance. Specifically, trading volume and transaction timing exhibit statistically significant effects, while inflation and the BI Rate do not show a significant impact on NAV. These results suggest that fund performance is more sensitive to internal market dynamics than to macroeconomic indicators.